Manajemen Perencanaan Pengembangan Kompetensi Pedagogik Guru Kelas Dalam Meningkatkan Kualitas Pembelajaran Peserta Didik (Studi Kasus di SDN Se-Kecamatan Cipaku Kabupaten Ciamis) - Endah Rekawat; Kusnandi Kusnandi; Lilis Kholisoh (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The quality of student learning is not yet optimal, this is in accordance with empirical data that the decline in achievements achieved by students in the academic and non-academic fields and the lack of professional teaching graduates means that planning management for developing teacher pedagogical competence is needed. The research was conducted using a descriptive analysis method with a qualitative design. The data analysis technique used is an interactive analysis technique, through data reduction, data presentation, drawing conclusions, and triangulation. The results of the research inform that (1) Planning for the development of pedagogical competence at SDN 2 Cieurih, SDN 3 Cieurih and SDN 1 Jalatrang was made based on the results of identifying needs and vision, mission and goals that had been determined, in its implementation the planning for developing teacher pedagogical competence was carried out in the form of meetings Work. (2) Implementation of pedagogical competency development at SDN 2 Cieurih, SDN 3 Cieurih and SDN 1 Jalatrang by participating in teaching, learning and administrative meetings, scientific forum programs held by local agencies in the form of education and training, making lesson plans, KKG, seminars or workshops . (3) evaluation Planning for the development of pedagogical competence focuses more on evaluating teacher performance through supervision activities with classroom action assessments. Apart from that, the principal also holds monthly work evaluations, one of which discusses the activities that have been carried out by teachers after participating in scientific forum activities outside the school. The monthly meeting is a control over the implementation of activities that will be carried out as well as an evaluation of activities that have been carried out previously. (4) Follow-up to the development of teacher pedagogical competence is to give awards to teachers who have met standards, provide coaching by holding meetings between school principals and teachers through face-to-face meetings and implementing the MGMP (Subject Teachers' Conference) program. ) (5) Supporting factors, namely teaching staff with a bachelor's degree, available funds, and complete infrastructure. Meanwhile, the inhibiting factor is that a handful of teachers who are approaching retirement have difficulty or are less interested in activities to develop the competence of teaching staff, in addition to having problems with timing at the same time as teaching schedules.